Displaying Language Diversity on the European Dictionary Portal – COST-Enel-Case Study on Colours and Emotions and their cultural references - Dorn, Amelie (2018)
In this paper we present a case study on colour and emotion terms and their cultural references in the framework of the COST European Network of e-Lexicography (ENeL), working towards Pan-European lexicography. We take an initial use case of red in connection with emotions (anger) and look at its roots across different European languages, including Russian. Our data model offers the possibility of connecting these fields in the context of digital lexicography using markup for etymological information with description standards like ONTOLEX or TEI. This is particularly relevant for using and displaying such data on the European Dictionary Portal, potentially offering access to detailed diachronic and synchronic lexicographic knowledge across a variety of languages.